The Wealth Effect in WTO Dispute Settlements: Analyzing International Economic Law as a Normal Good - Raut, Shilpa Samplonis; Oviedo, Alexis (European Scientific Journal, ESJ, 2024)
The objective of the article is to introduce a theoretical endeavor aimed at evaluating the potential validity of empirical results within the realm of economic theory. The existing literature and empirical evidence indicate that wealthier participants within the World Trade Organization exhibit a propensity for regular engagement with dispute settlement mechanisms in the field of international economic law. This uneven pattern of utilization of the dispute settlement mechanism implies that the global institution, serving as a provider of global public goods within an economic context, assumes attributes akin to a normal good. The article argues that the discrete nature of the global public good leads to the normal characteristics of the good. The individual actions of member countries in the form of initiation of dispute are expected to contribute to promoting transparent trade flow because the respondent countries need to remove the trade obstacles. The authors aim to pinpoint the essential concepts and assumptions pertinent to International Economic Law and its application within the World Trade Organisation through synthesizing and analyzing existing literature, This methodological approach seeks to foster comprehension of the empirical patterns. The authors apply the pay-off matrix to the dispute settlement unit of any two member countries and explain to understand the relatively lower use of the dispute settlement unit by low-income countries. The result shows the need for structural change in the multilateral trade organisation if it were to keep itself relevant by meeting the demands.